3D effects of clouds on the solar radiation at the surface and variation of cloud properties in two characteristic sites of Brazil - Santana, Jorge Rosas (2025)
Effective cloud optical depth (ECOD) retrievals were conducted for the period of 2012-2018 at two characteristic sites: the Metropolitan Area of São Paulo (MASP) and in Manaus, around a preserved rainforest, in the Amazon, representing an urban and a pristine environment, respectively. Additionally, the impact of 3D cloud effects on shortwave radiation at the surface was evaluated using various cloud field geometries. The study highlights the importance and the multifunctionality of Multifilter Rotating Shadowband Radiometers (MFRSR), which enable ECOD estimation and also allowing the development of ancillary algorithms to classify different retrieval scenarios, including overcast conditions and sun-disk blocked by clouds. The evaluation of methodologies confirms the feasibility of classifying overcast conditions using MFRSR and if the sun-disk is clear or cloudy. Statistical differences in ECOD between the Manaus (mean value of 31.1) and São Paulo (mean value of 32.8) were observed throughout the entire period. The most significant differences occurred in spring, with a mean ECOD of 27.8 in Manaus and 35.7 in São Paulo. Those differences probably can be attributed to changes in microphysical properties of the clouds, due to the combination of moisture convection with aerosol particles transported from other regions during the biomass burning season. A case study of the transport of aerosol from biomass burning toward São Paulo revealed strong radiative impacts with solar irradiance dropping to 0 and estimated ECOD values as high as 300. In addition, the cloud radiative effects at the surface was 7% stronger on the biomass burning day as compared to other overcast days. The 3D effects of cloud fields were assessed using 3D simulations and compared with 1D simulations of Individual Pixel Approximations (IPA). For this purpose, we used various 3D clouds geometries, such as a single cuboid cloud, stochastic stratocumulus clouds and near-realistic cumulus clouds from Large Eddy Simulations (LES) in the Amazon. The cloud fields were used as input for the Monte Carlo code for the physically correct tracing of photons in cloudy atmospheres (MYSTIC), a state of art of 3D radiative transfer model. Results showed the complexity of the 3D effects mainly influenced by the solar geometry, cloud optical depth, cloud thickness, and surface albedo. Using one cuboid cloud, strong impacts of the surface albedo and the cloud thickness were observed. While the increase of surface albedo helped to increase the positive values of the 3D effects, the increase of cloud thickness enhanced the effect of shadowing, contributing to more negative values of 3D effects. In general, for cloud fields analyzed, the 3D effects on the global downward irradiance were negative, as observed in cuboid cloud fields (minimum of -40 % at optically thick clouds) and LES simulations (minimum of -16 %), but shallow stochastics stratocumulus clouds exhibited positive values (maximum of 10 %). Variations in cloud fraction, solar geometry, and ECOD were also identified as key mechanisms driving the 3D effects in broken cloud fields.